1997
DOI: 10.1074/jbc.272.50.31308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intravesicular H+ and Extracellular H+ and Zn2+ on Insulin Secretion in Pancreatic Beta Cells

Abstract: The effects of extracellular Zn 2؉ and pH and intravesicular pH on insulin and 5-hydroxytryptamine (5-HT) secretion from pancreatic beta cells were investigated. Insulin and 5-HT secretion from single cells was detected by amperometry as a series of current spikes corresponding to detection of multimolecular packets secreted by exocytosis. Spike width was used as a measure of the kinetics of clearance from the cell and the area of spikes as a measure of amount released. Changes in extracellular pH from 6.9 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(127 citation statements)
references
References 57 publications
(68 reference statements)
7
120
0
Order By: Relevance
“…We estimate that granular pH is above 6.0 under these conditions. Bafilomycin has been reported not to affect immediate (Ͻ60 s) exocytosis of insulin granules as measured by amperometry in canine ␤-cells (50) but to inhibit insulin release from permeabilized INS-1 cells (51). In our hands, bafilomycin markedly inhibited glucose-induced insulin secretion by mouse islets but also impaired the glucose-induced [Ca 2ϩ ] c rise (not shown), as in MIN6 cells (52).…”
Section: Characteristics Of the Ph-sensitive Probe Lysosensor Dnd-160-supporting
confidence: 49%
“…We estimate that granular pH is above 6.0 under these conditions. Bafilomycin has been reported not to affect immediate (Ͻ60 s) exocytosis of insulin granules as measured by amperometry in canine ␤-cells (50) but to inhibit insulin release from permeabilized INS-1 cells (51). In our hands, bafilomycin markedly inhibited glucose-induced insulin secretion by mouse islets but also impaired the glucose-induced [Ca 2ϩ ] c rise (not shown), as in MIN6 cells (52).…”
Section: Characteristics Of the Ph-sensitive Probe Lysosensor Dnd-160-supporting
confidence: 49%
“…The 5-HT method was used instead of direct detection of insulin at a modified electrode (23) because of the relative simplicity of this approach, especially for autocrine studies. The validity of the 5-HT method has been established by previous studies that demonstrated: 1) detection of exocytosis with a variety of insulin secretogogues (24,28,29); 2) that insulin and 5-HT are released exclusively from the same vesicles (30); and 3) that direct detection of insulin and detection of 5-HT give comparable results for insulin stimulation (18). As seen in Fig.…”
Section: Requirement Of Intracellular Ca 2ϩ Mobilization For Insulinsmentioning
confidence: 88%
“…Amperometric Detection of Exocytosis-Microelectrodes were constructed of carbon fibers sealed in glass micropipettes and were polished to a 45°angle and cleaned prior to use (23,24). Amperometric measurements were made by positioning microelectrodes ϳ1 m from a cell and applying stimulant from a micropipette ϳ 30 m from the cell as described elsewhere (23,24 Amperometry was performed using a battery to apply potential to a sodium-saturated calomel reference electrode as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amperometry is useful in monitoring secretion from single cells, even at the level of single exocytotic events, because it allows detection of attomole quantities with millisecond temporal resolution (Wightman et al, 1991;Chow et al, 1992). Amperometry has been applied to (3-cells either by using a ruthenium oxide/cyanoruthenate-coated microelectrode to directly detect insulin (Huang et al, 1995;Aspinwall et al, 1997) or by using a carbon fiber microelectrode to detect 5 -hydroxytryptamine that had been allowed to accumulate in the secretory vesicles (Smith et al, 1995;Zhou and Misler, 1996). A limitation of amperometry is that a microelectrode is inherently a single-point sensor, meaning that measurements are made at one location on a cell with a detection area determined by the size of the electrode Recent advances in fluorescence imaging have resulted in new approaches to monitor exocytosis with a non-invasive method.…”
mentioning
confidence: 99%